First record of Camponotus brettesi Forel, 1899 (Hymenoptera: Formicidae: Formicinae) from Brazil - Harada, Ana Yoshi; Ferreira, Tayana Maria Cabral; Fernandes, Marcus Emanuel Barroncas; Castro, Rodrigo Baia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Camponotus brettesi belongs to an ant genus with high species richness and abundance around the world, and here it is recorded for the first time in northern Brazil. Until now, this species is known from open fields, farms, primary and secondary forests, in lowland and upland Central American and in the northeast of South America, varying from 10 to 1160 m in elevation, occurring from Mexico to Venezuela, including the Galapagos, Trinidad and Tobago Islands. The specimens reported here were collected in arboreal pitfall traps with sardine and sugary baits in a mangrove forest on the Amazonian coast in the municipality of Bragança, Para, Brazil. This record represents the southern-most occurrence for this species, extending its distribution about 2.200 km to the south in the Neotropics and approximately 2.000 km to the east of South America in Brazil.